"Affluence of the Heart": Wastefulness and the Search for Meaning in Millennial Japan. Issue 1 (27th February 2014) - Siniawer, Eiko Maruko
<x content-type="archive" xml:space="preserve">Abstract</x> In the first decade of the twenty-first century, Japan experienced a surge in the evocation of the word "mottainai, " most simply translated as "wasteful." Children's literature, mass-market nonfiction, magazines, newspapers, songs, government ministries, corporations, and nongovernmental organizations deliberately used and defined the term as they took up the question of what was to be deemed wasteful. This essay examines how discourses that were ostensibly about wastefulness constituted an articulation of values, a search for meaning and identity, and a certain conception of affluence in millennial Japan. It suggests that this idea of mottainai reflected wide-ranging principles and beliefs that were thought to define what it meant to be Japanese in the twenty-first century, at a time when there settled in an uneasy acceptance of economic stagnation and a desire to find meaning in an economically anemic, yet still affluent, Japan.